Analysis of the Status of Financial Resources for Community Education Programmes in Tanzania - Mbughi, Benjamin (Papers in Education and Development, 2022)
Abstract This study analysed the status of financial resources for community education programmes in Tanzania. Purposive sampling was used to generate data from a total of 41 participants. Data were analysed thematically with the help of MAXQDA software. The findings of this study revealed that insufficient funds were disbursed for community education programmes. Further, it was disclosed that the nature of leadership determined the manner and pace in which funds were to be released. The study indicates that the delay of disbursement of funds sometimes significantly hampered the implementation of community education programmes. The study recommends that investment in both formal and non-formal education should be the central agenda if developing countries like Tanzania need to attain sustainable community development. Keywords: community education, budget, financial resources